2022
DOI: 10.1039/d2sm01169g
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic sol–gel transition: the influence of sample thickness, pressure and strain

Abstract: We demonstrate an unprecedented influence of sample thickness (d) and pressure (P) on gelation of a liquid crystalline nematic host. The temperature at which the anisotropic nematic sol transforms to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…As stated in the introduction section, for samples thinner than a critical value, the sol–gel temperature ( T sg ) has been seen to be strongly dependent on the sample thickness. 15 Presuming that such a feature could be arising owing to confined geometry features, we looked at the effect on T sg caused by the presence of the polymer strands. The thermal variation of the transmitted laser intensity, employed to determine T sg is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in the introduction section, for samples thinner than a critical value, the sol–gel temperature ( T sg ) has been seen to be strongly dependent on the sample thickness. 15 Presuming that such a feature could be arising owing to confined geometry features, we looked at the effect on T sg caused by the presence of the polymer strands. The thermal variation of the transmitted laser intensity, employed to determine T sg is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Physical gels that combine the anisotropic character of LCs and the mechanical rigidity of the thermoreversible network have been reported to present significant consequences on the LC-gel (LCG) properties, faster electro-optic response, anomalous variations in elastic constants, enhanced photoluminescence, and applications in soft robotics and flexible displays. [10][11][12][13][14][15][16][17] We have just reported 15 the novel influence of sample thickness and applied pressure on the characteristics of an organogel exhibiting a nematic-to-nematic-gel transition. It was found that the gelation temperature (T sg ) depends strongly on the sample thickness d, for d o 30 mm.…”
Section: Introductionmentioning
confidence: 99%